تحليل بيئة الأعمال الخارجية لإنشاء صناديق الوقف النقدي في الجزائر وفق نموذج PESTEL: تحليلات ومقترحات - قداوي، عبدالقادر (المركز الجامعي عبدالحفيظ بوالصوف ميلة - معهد العلوم الاقتصادية والتجارية وعلوم التسيير, 2023)
تستهدف هذه الدراسة تحليل بيئة الأعمال الخارجية لاكتشاف فرص وتهديدات إنشاء صناديق الوقف النقدي في الجزائر على ضوء نموذج (PESTEL)، وابتداء بتعريف مفاهيم ومصطلحات الدراسة ومرورا على شرح النموذج والتعرف على مكوناته الستة، وقفنا مطولا عند تحليل الوضع الراهن للجزائر، طلبا لاستنطاق ظروف البيئة الخارجية حتى نتمكن من الوصول إلى نتائج توضح إمكانية إنشاء الصندوق من عدمه. وخلصت الدراسة بعد الوقوف على تحليل العوامل السياسية والاقتصادية والاجتماعية والتكنولوجية والبيئية والقانونية ومعرفة علاقاتها وآثارها، أن البيئة مناسبة والفرصة سانحة وأغلب المتغيرات الخارجية معينة، خصوصا بعد إنشاء الديوان الوطني للأوقاف والزكاة باعتباره مؤسسة وقفية مستقلة تعني بتطوير الوقف وترقية أدواته ووسائله وتجويد مخرجاته واستدامة آثاره، بما يحقق أمثل تنمية اجتماعية وخيرية واقتصادية، وفق أحسن السياسات وأصوب المسارات. This study aims to analyzing the external business environment to discover the opportunities and threats of establishing cash waqf funds in Algeria in the light of the (PESTEL) model, Starting with defining the concepts and terminology of the study, passing through the explanation the model and identifying its six components, we stopped at length to analyzing the current situation in Algeria, in order to investigate the conditions of the external environment so that we can reach results that show the possibility of establishing the fund or not. The study concluded, after examining the analysis of political, economic, social, technological, environmental and legal factors and knowing their relationships and effects, that the environment is suitable, the opportunity is favorable, and most of the external variables are helped, especially after the establishment of the National Office of waqf and Zakat as an independent waqf institution concerned to develop the waqf and the promotion of its tools and sustainability of its effects, including It achieves optimal social, charitable and economic development, according to the best policies and the right paths.
Keywords: الصناديق الوقفية -- بيئة الأعمال -- المؤسسات الوقفية -- الجزائر